Gestión administrativa y su incidencia en el desempeño laboral del Gobierno Autónomo Descentralizado del Cantón Vinces - Perez Jalca, Alexa Virginia (2018)
In the Autonomous Decentralized Government of the Canton Vinces administrative management is a subject of criticism and much evaluation for a long time in the various administrations that this has had and the incidence that the quality of the administrative management by the main officials produces in the work performance of all the staff that works in said institution, however, with this research project is intended to apply techniques that favor the development of leadership and work performance.